European tax law - Terra, B. J. M (Kluwer Law International, 2008)
This book is intended as a reference book for tax law and EC law pratitioners, tax administrators, academics, the judiciary and tax or Community law policy makers. The book offers a systematic survey of the tax implications of the EC Treaty and of European integration and of the EC tax harmonization policy, a discussion of the Community tax rules in force, and a discussion of the EC Court s case law in tax matters. Its contents may be divided into six main themes